2019
DOI: 10.3390/md17050287
|View full text |Cite
|
Sign up to set email alerts
|

Flaccidoxide-13-Acetate-Induced Apoptosis in Human Bladder Cancer Cells is through Activation of p38/JNK, Mitochondrial Dysfunction, and Endoplasmic Reticulum Stress Regulated Pathway

Abstract: Flaccidoxide-13-acetate, an active compound isolated from cultured-type soft coral Sinularia gibberosa, has been shown to have inhibitory effects against invasion and cell migration of RT4 and T24 human bladder cancer cells. In our study, we used an 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT), colony formation assay, and flow cytometry to determine the mechanisms of the anti-tumor effect of flaccidoxide-13-acetate. The MTT and colony formation assays showed that the cytotoxic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…Interestingly, only the compound SCM9 inhibited LPS-induced TNF α production which suggests its anti-inflammatory character. The changes in the expression of signaling molecules by SCM9 in Jurkat cells, such as 2× increase in JNK and an increase in p38α may indicate a proapoptotic action of the compound towards T cells associated with changes in MAP kinase expression [34,35]. However, it is intriguing that the signaling pathways induced by the compound did not involve caspase, NFκB, BcL-2 and Fas pathway despite very strong immunosuppressive properties of SCM9 towards WEHI-231.…”
Section: Compoundmentioning
confidence: 96%
“…Interestingly, only the compound SCM9 inhibited LPS-induced TNF α production which suggests its anti-inflammatory character. The changes in the expression of signaling molecules by SCM9 in Jurkat cells, such as 2× increase in JNK and an increase in p38α may indicate a proapoptotic action of the compound towards T cells associated with changes in MAP kinase expression [34,35]. However, it is intriguing that the signaling pathways induced by the compound did not involve caspase, NFκB, BcL-2 and Fas pathway despite very strong immunosuppressive properties of SCM9 towards WEHI-231.…”
Section: Compoundmentioning
confidence: 96%
“…Thymoquinone, the major active compound of black seed oil, exhibits cytotoxicity to bladder cancer cells and induces apoptosis by upregulating the phosphorylated eIF2α, IRE1, and CHOP (Zhang et al, 2018). Similarly, flaccidoxide-13-acetate, isolated from cultured soft coral Sinularia gibberosa, was found to provoke ERS and activate the PERK-eIF2α-ATF6-CHOP pathway, causing inhibitory effects against the invasion and migration of bladder cancer cells (Wu et al, 2019b). Yuan et al (2013) found that exposure to licochalcone A (a licorice chalconoid) could induce apoptosis in T24 bladder cancer cells by enhancing GRP78 and CHOP expression.…”
Section: Ers and Bladder Cancer Cell Apoptosismentioning
confidence: 99%
“…A cembrane-type diterpenoid, flaccidoxide-13-acetate, isolated from marine soft coral Sinularia gibberosa, has been suggested to induce apoptosis in human bladder cancer cells [14]. To our knowledge, its effect on HCC remains to be confirmed.…”
Section: Introductionmentioning
confidence: 96%